Wireless sensing modules for rural monitoring and precision agriculture applications. Issue 1 (2nd January 2018) - Tan Lam, Phat; Quang Le, Tan; Nguyen Le, Ngan; Dat Nguyen, Son
ABSTRACT: In this work, a new design of wireless sensing modules for the wireless sensor network was proposed and the specifications were tested ( Received Signal Strength Indicator – RSSI, Packet Reception Ratio – PRR, Link Quality Indicator – LQI) in comparison with some commercial products. Indeed, we focus on the design of wireless sensing nodes and programming of the data transfer protocol for wireless sensing nodes (from the PHYSICAL layer to MAC layer) Experimental results show that the designed wireless sensing modules have the potential for real-world application with read-range (over 150 m), RSSI (bigger than –80 dBm), LQI (bigger than 108) and PRR (over 99%) in the range between 0 and 150 m.